Kinetic Adsorption Study of Cd(II) Metal Ions Using Glutaraldehyde-Crosslinked Thiosemicarbazide-Modified Poly (vinyl alcohol) - Hannifa Puspawardhani Rifa’i; Muhammad Ali Zulfikar (Jurnal Serambi Engineering, 2024)
Cd(II) metal ions are commonly found in water bodies and are non-essential and carcinogenic, leading to lung cancer. Thus, it is crucial to remove Cd(II) metal ions from water. Adsorption is one effective separation method due to its relative simplicity and cost-effectiveness. In this work, the adsorption kinetics study of Cd(II) metal ions using PVA.cl.GA-TSC were examined. Polyvinyl alcohol (PVA) was crosslinked with glutaraldehyde and subsequently modified with thiosemicarbazide (TSC). The resulting PVA.cl.GA-TSC was characterized using FTIR. The adsorption process was carried out in a batch system at room temperature. The study revealed that the adsorption kinetics of Cd(II) metal ions with PVA.cl.GA-TSC followed a pseudo-second-order kinetic model, with a rate constant of 0.4 × 10⁻³ g.mg⁻¹.min⁻¹. In the kinetics data, an intra-particle diffusion model was also performed to understand the adsorption reaction mechanism. The intra-particle diffusion model indicated that the rate-determining step was governed by the intra-particle diffusion stage, with a rate constant of 0.387 mg.g-1min-1/2.